A latent class analysis of young adult gamblers from the Manitoba Longitudinal Survey of Young Adults. Issue 1 (2nd January 2019) - Dowd, Damien A.; Keough, Matthew T.; Jakobson, Lorna S.; Bolton, James M.; Edgerton, Jason D.
ABSTRACT: Informed by the Pathways Model, the current study utilized latent class analysis (LCA) to empirically derive subtypes of gamblers based on measures of impulsivity, anxiety, depression, drug use and alcohol dependence. The sample in this study ( N  = 566) was comprised of young adult gamblers (18–22 years of age) who participated in the Manitoba Longitudinal Survey of Young Adults (MLSYA). Multinomial regression was utilized to examine how demographic variables and participant scores on the Problem Gambling Severity Index (PGSI) predicted membership in gambler classes from the LCA. Results of the LCA revealed three classes of gamblers: emotionally vulnerable, non-problem and impulsive . Multinomial regression showed that older age (i.e. 20–22 years of age), lower income (< $20, 000 per year), living independently and PGSI scores were associated with increased odds of being classified as an impulsive gambler. Identifying as European, living independently and PGSI scores were associated with increased odds of being grouped in the emotionally vulnerable class of gambler. These results suggest that young adult gamblers are not a homogeneous group but instead are best understood as falling into different subtypes based on shared characteristics outlined in the Pathways Model.